The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1399-3054.2008.01086.x
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between the photosynthetic activity and the performance of Cakile maritima after long‐term salt treatment

Abstract: Cakile maritima is a halophyte with potential for ecological, economical and medicinal uses. We address here the impact of salinity on its growth, photosynthesis and seed quality. Whole plant growth rate and shoot development were stimulated at moderate salinity (100-200 mM NaCl) and inhibited at higher salt concentrations. Although diminished in the presence of salt, potassium and calcium uptake per unit of root biomass was maintained at relatively high value, while nutrient-use efficiency (NUE) was improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 62 publications
(86 reference statements)
7
26
0
2
Order By: Relevance
“…S treatment suggests the implication of these pigments in the antioxidant response. Indeed, anthocyanins are potent antioxidants known for their protective role against photoinhibiton in stressed plants (Debez et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…S treatment suggests the implication of these pigments in the antioxidant response. Indeed, anthocyanins are potent antioxidants known for their protective role against photoinhibiton in stressed plants (Debez et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of chlorophyll a (Chl a) fluorescence is a rapid and noninvasive tool used to screen varieties for salinity tolerance. Previous reports of NaCl effects on Chl a fluorescence suggested that F v /F m was not a useful indicator of salt stress (Santos 2004;Jiang et al 2006;Debez et al 2008;Degl'Innocenti et al 2009;Hichem et al 2009). In contrast, other authors (Misra et al 2001;Lu et al 2003a, b;Netondo et al 2004;Demiral and Türkan 2006) reported that F v /F m was an early indicator of salt stress.…”
Section: Abbreviationsmentioning
confidence: 96%
“…Actually, F v /F m values (up to 0.75) over the salinity range were close to those considered as typical to healthy nonstressed leaves (0.75-0.85) (Vassilev and Manolov, 1999). Hence, B. maritima was able to maintain the photosynthetic-apparatus integrity, even at salinity levels exceeding that of seawater, which demonstrates a very high degree of salinity tolerance relative to other halophytic species (Redondo-Gómez et al, 2006;Debez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%